Pertanggungjawaban Maskapai Penerbangan Terhadap Kehilangan Barang Bawaan (Bagasi) Berdasarkan Undang-Undang Nomor 1 Tahun 2009 Tentang Penerbangan - Alex Candra; Muhamad Japri; Romanius (Collegium Studiosum Journal, 2021)
How would we feel if after a long long trip, sitting on a plane for hours, the only thing we really wanted was to get to our destination quickly to rest. But what if after a long wait for the luggage to come out, it turns out that you can't find our suitcase in the plane's baggage line. Checked baggage is passenger goods handed over to the carrier (airline) to be transported by the same aircraft. Meanwhile, cabin baggage is goods carried by passengers and is under the control of the passengers themselves. Basically, if there is a loss of baggage during that time, legally each airline is responsible for any loss due to loss of baggage during the flight. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed.